A rare presentation of common tropical fever, scrub typhus-purpura fulminans, lower limb arterial thrombosis and pulmonary artery thrombosis - Bandyopadhyay, Arko; Vyawahare, Milind S.; Sakhale, Jayanth (International Journal of Research in Medical Sciences, 2023)
Purpura fulminans (PF) is an acute emergency condition manifested as purpuric rash secondary to thrombosis of microvasculature. It is rapidly progressive, can cause thrombosis in large as well as small vessels and tissue infarction. Although it is commonly associated with Meningococcal and Streptococcal infections, here we report this case of PF associated with scrub typhus infection. Our patient presented with generalised body rash and progressed to multiorgan dysfunction. On evaluation, common causes of PF were ruled out and eventually patient came out to be IgM scrub typhus serology kit test positive. Lower limb angiography and pulmonary artery angiography revealed vascular thrombosis. The patient started on IV antibiotics, other supportive managements, anticoagulation. Later the patient improved clinically, skin rash resolved with excoriations but developed gangrenous changes in both lower limbs. Hence the uncommon presentation of scrub typhus infection as purpura fulminans needs early identification and effective treatment to achieve mortality and morbidity benefit.